2021
DOI: 10.1289/ehp9285
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Cholinesterase Inhibition: Developmental Neurotoxicity of Organophosphate Ester Flame Retardants and Plasticizers

Abstract: Background: To date, the toxicity of organophosphate esters has primarily been studied regarding their use as pesticides and their effects on the neurotransmitter acetylcholinesterase (AChE). Currently, flame retardants and plasticizers are the two largest market segments for organophosphate esters and they are found in a wide variety of products, including electronics, building materials, vehicles, furniture, car seats, plastics, and textiles. As a result, organophosphate esters and their metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 129 publications
(260 reference statements)
0
22
0
Order By: Relevance
“…In addition to carcinogenicity, , developmental and reproductive toxicity, and endocrine disruption, , growing evidence from laboratory animal studies and human epidemiological studies has indicated that tri-OPEs cause significant neurotoxicity . For example, exposure of zebrafish/Chinese Rare Minnows to tri­(2-chloroethyl)­phosphate (TCEP), tri­(1,3-dichloro-2-propyl)­phosphate (TDCIPP), tri-phenyl phosphate (TPHP), tri- n -butyl processes phosphate (TNBP), or tri­(2-butoxyethyl)­phosphate (TBOEP) induced hyperactivity, impaired learning/memory performance, and led to significant changes in locomotor behavior .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to carcinogenicity, , developmental and reproductive toxicity, and endocrine disruption, , growing evidence from laboratory animal studies and human epidemiological studies has indicated that tri-OPEs cause significant neurotoxicity . For example, exposure of zebrafish/Chinese Rare Minnows to tri­(2-chloroethyl)­phosphate (TCEP), tri­(1,3-dichloro-2-propyl)­phosphate (TDCIPP), tri-phenyl phosphate (TPHP), tri- n -butyl processes phosphate (TNBP), or tri­(2-butoxyethyl)­phosphate (TBOEP) induced hyperactivity, impaired learning/memory performance, and led to significant changes in locomotor behavior .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies on exposure to organophosphates are also gaining ground, especially when it comes to the early stages of development, when organophosphates may have greater consequences [115].…”
Section: Toxicological Effectsmentioning
confidence: 99%
“…Although various in vitro and in vivo studies have investigated the negative health effects of OPE exposure (7)(8)(9), human data results on adult OPEs and NAFLD are still relatively scarce. Given the prevalence of OPEs in the environment and their potential deleterious consequences, investigating their impact on the incidence and progression of NAFLD is vital.…”
Section: Introductionmentioning
confidence: 99%
“…OPEs can be found in a variety of products, including electronics, building materials, automobiles, furniture, vehicle seats, plastics, and textiles. As a result, OPEs and their metabolites are now commonly discovered in human urine, blood, placental tissue, and breast milk worldwide ( 8 ). Concerns about OPEs have grown in recent years, and previous research revealed that OPEs can have a variety of negative impacts on creatures and people, including poor reproductive health and birth outcomes, obesity, neurodevelopment, hypertension, and sex steroid hormones ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%